Children, Deafness, and Deaf Cultures in Popular Media - Yenika-Agbaw, Vivian S.; Stephens, John, 1972- (Book collections on Project MUSE., 2023)
"Children, Deafness, and Deaf Cultures in Popular Media examines how creative works have depicted what it means to be a deaf or hard of hearing child in the modern world. In this collection of critical essays, scholars discuss works that cover wide-ranging subjects and themes: growing up deaf in a hearing world, stigmas associated with deafness, rival modes of communication, friendship and discrimination, intergenerational tensions between hearing and nonhearing family members, and the complications of establishing self-identity in increasingly complex societies. Contributors explore most of the major genres of children's literature and film, including realistic fiction, particularly young adult novels, as well as works that make deft use of humor and parody. Further, scholars consider the expressive power of multimodal forms such as graphic novel and film to depict experience from the perspective of children. Representation of the point of view of child characters is central to this body of work and to the intersections of deafness with discourses of diversity and social justice. The child point of view supports a subtle advocacy of a wider understanding of the multiple ways of being D/deaf and the capacity of D/deaf children to give meaning to their unique experiences, especially as they find themselves moving between hearing and Deaf communities. These essays will alert scholars of children's literature, as well as the reading public, to the many representations of deafness that, like deafness itself, pervade all cultures and are not limited to specific racial or sociocultural groups"--